The Effects of Environmental Information Disclosure and Energy Types on the Cost of Equity: Evidence from the Energy Industry in China. - Fonseka, Mohan; Rajapakse, Theja; Tian, Gao‐Liang (Abacus, 2019)
This study investigates whether environment information disclosure (EID) and different energy sources have any effect on the cost of equity capital (COEC), and how the EID effect on the COEC varies with different types of energy. We find a negative relationship between EID and COEC. Thus, EID reduces the agency problem and information asymmetry between firms and investors, and also supports the legitimacy and stakeholder theories' explanation of the effect of EID on the COEC in China. We find a positive (negative) relationship between some energy sources such as gas, fossil‐fuelled thermal power generation, and oil (hydro‐power generation, solar, and wind) and the COEC. The finding explains the polluting nature, risk of replacement, regulation risk, and regulatory costs of different energy types, and those risks have been accounted by investors. We also find that when gas, fossil‐fuelled thermal power, and oil firms increase their level of EID, their COEC increases, whereas when power grid, solar, and wind power firms increase their level of EID, their COEC decreases. This finding is supported by the combination of polluting nature, risk of replacement, regulation risk, and regulatory costs of different energy sources and legitimacy and stakeholder theories. Our findings are robust to several endogeneity checks and additional tests for several unique features of Chinese capital markets.